Acute skin toxicity associated with a 1-week schedule of whole breast radiotherapy compared with a standard 3-week regimen delivered in the UK FAST-Forward Trial. Issue 1 (July 2016) - Brunt, A. Murray; Wheatley, Duncan; Yarnold, John; Somaiah, Navita; Kelly, Stephen; Harnett, Adrian; Coles, Charlotte; Goodman, Andrew; Bahl, Amit; Churn, Mark; Zotova, Rada; Sydenham, Mark; et al.
Abstract: Background and purpose: FAST-Forward is a phase 3 clinical trial testing a 1-week course of whole breast radiotherapy against the UK standard 3-week regimen after primary surgery for early breast cancer. Two acute skin toxicity substudies were undertaken to test the safety of the test schedules with respect to early skin reactions. Material and methods: Patients were randomly allocated to 40 Gy/15 fractions (F)/3-weeks, 27 Gy/5F/1-week or 26 Gy/5F/1-week. Acute breast skin reactions were graded using RTOG (first substudy) and CTCAE criteria v4.03 (second substudy) weekly during treatment and for 4 weeks after treatment ended. Primary endpoint was the proportion of patients within each treatment group with grade ⩾3 toxicity (RTOG and CTCAE, respectively) at any time from the start of radiotherapy to 4 weeks after completion. Results: 190 and 162 patients were recruited. In the first substudy, evaluable patients with grade 3 RTOG toxicity were: 40 Gy/15F 6/44 (13.6%); 27 Gy/5F 5/51 (9.8%); 26 Gy/5F 3/52 (5.8%). In the second substudy, evaluable patients with grade 3 CTCAE toxicity were: 40 Gy/15F 0/43; 27 Gy/5F 1/41 (2.4%); 26 Gy/5F 0/53. Conclusions: Acute breast skin reactions with two 1-week schedules of whole breast radiotherapy under test in FAST-Forward were mild.